Análise produtiva e econômica de clones de seringueira submetidos a diferentes frequências de sangrias - Corredato, Roberto Aparecido (2011)
This work had as objective the productive and economic analysis of clones of seringueira (Hevea brasiliensis) submitted the different frequency of bleeding. The experiment was installed in the City of Indianópolis - PR. For accomplishment of the study it was used four clones of seringueira in production the 12 years, in espaçamento of 8,0m x 4,0m. Clones studied had been PB235, IAN873, GT1 and RRIM600, and the treatments had constituted of systems of bleeding in form of half spiral with frequency of bleeding to each three days, each four days and each five days, with ten repetitions (trees), for a period of three months/harvest. The collection of the data occurred at two times, 2009/2010 harvest and harvest 2010/2011, becoming fullfilled six evaluations, with the register of the latex productivity (g tree-1 month-1) coagulado of course in the earthen bowls of harvest. For accomplishment of the economic analysis the used data had been the gotten ones and practising in the area of the present work. Clones studied PB 235, IAN 873, GT1 and RRIM 600 had not presented increase in the latex productivity with the increase of the bleeding frequency. Clone PB235, in reduced frequency presented a net revenue 40% greater that clone IAN873, 30% greater that clone GT1 and 15% greater that clone RRIM600. Clone RRIM600 in reduced frequency presented a net revenue 30% greater that clone IAN873 and 18% greater that clone GT1. Clone GT1 in reduced frequency presented a net revenue 14% greater that clone IAN873. Clone IAN873 in reduced frequency presented the lesser net revenue. The annual net revenue in the present work is bigger in reduced frequency for clone PB235, followed for clones RRIM600, GT1 and clone IAN873